Moore state machine for adaptive modulation and coding in high‐speed railway LTE‐R systems. Issue 9 (4th April 2016) - Zhao, Yisheng; Chen, Zhonghui; Ji, Hong
Abstract : An adaptive modulation and coding (AMC) scheme based on a Moore state machine is proposed for the high‐speed railway communication systems. By setting a buffer zone for the signal‐to‐noise ratio threshold value, the proposed scheme is able to reduce the frequent transition of the modulation and coding scheme. Simulation results show that the proposed AMC strategy has a more stable spectral efficiency than the traditional AMC method using a piecewise function.